Recent Advances in Synthesis and Study of 2D Twisted Transition Metal Dichalcogenide Bilayers. Issue 5 (11th May 2021) - Tang, Bijun; Che, Bingyu; Xu, Manzhang; Ang, Zhi Peng; Di, Jun; Gao, Hong-Jun; Yang, Haitao; Zhou, Jiadong; Liu, Zheng
Abstract : Transition Metal Dichalcogenide Bilayers The cover page schematically illustrates the twisted transition metal dichalcogenides (t‐TMDs) bilayer and the associated Moiré superlattices which may give rise to exotic physical phenomena. In article number 2000153 by Haitao Yang, Jiadong Zhou, Zheng Liu and co‐workers, an update‐to‐date overview of the recent progress in the synthesis of t‐TMDs and the study of the associated properties are presented. Challenges and future research directions are also discussed in the light of recent advances in the field.